Methods for Evaluating the Elastic Properties of Stainless Steel Perforated Plates - Viktors Mironovs; Marija Osipova; Pavel Akishin; Vjcheslavs Zemchenkovs; Dmitrijs Serdjuks (Metals)
Perforated materials are widely used in various fields, including in medicine, for example, in trays for placing and storing cutting tools and for sterilizing disposable materials. Currently, the effective elastic modulus of orthopedic plates is higher than the effective elastic modulus of human bone tissue (the effective elastic modulus of bone ranges between 10 and 30 GPa, depending on the type of bone). This difference in effective elastic modulus leads to the phenomenon known as the stress shielding effect, where the bone experiences insufficient mechanical loading. One potential approach to influence the effective elastic modulus of orthopedic plates is through perforations in their design. Stainless steel 316L has garnered significant interest among medical engineering specialists due to its lower weight, higher strength, and superior biocompatibility. The elastic properties of perforated constructions are influenced by their internal quality, dimensions, shapes, and the overall perforation area, making their study important. An experiment was conducted on perforated plates of 316L stainless steel with perforation areas ranging from 3% to 20%. Increasing the perforation area in perforated 316L stainless steel plates (perforated plates had dimensions of 50 mm in height, 20 mm in width, and 1 mm in thickness; hole diameter of 1 mm; and pitch between the holes of 2, 3, 4, and 5 mm) from 3% to 20% resulted in a decrease in Young’s modulus of the perforated plates from 199 GPa to 147.8 GPa, determined using a non-destructive method for determining resonant frequencies using a laser vibrometer. A three-point bending test on the perforated plates confirmed these findings, demonstrating a consistent trend of decreasing Young’s modulus with increasing perforation area, from 194.4 GPa at 3.14% to 142.6 GPa at 19.63%. The three-point bending method was also employed in this study to determine the Young’s modulus of the perforated plates in order to reinforce the obtained results on the elastic properties by determining the resonance frequencies with a laser vibrometer. It was discovered that the Young’s modulus of a perforated plate cannot be determined solely by the perforation area, as it depends on both the perforation diameter and the pitch between the perforations. In addition, finite element method (FEM) simulations were conducted, revealing that increasing perforation diameter and decreasing pitch significantly reduce the Young’s modulus—with values dropping from 201.5 GPa to 72.6 GPa across various configurations.